VD_FINDINFO HC / 2016 / 484 vom 3. Mai 2016 - VD Tribunal cantonal (2016)
AVANCE DE FRAIS, VALEUR LITIGIEUSE, PRINCIPE DE LA BONNE FOI | 83 al. 2 LP, 91 al. 1 CPC (CH), 98 CPC (CH), 18 al. 1 TFJC (2010)